A Moderating Impact of ISO 14001 Certified Firms on Reverse Logistics Implementation: Analysis of A Second-Order Model - Fernando, Yudi; Muhammad Shabir, Shaharudin; Hasnah, Haron; Noorzihan, Abd Karim; Yuvaraj, Ganesan (Universiti Malaysia Sarawak (UNIMAS), 2018)
The aim of this study is to investigate the moderating impact of ISO 14001 certified firms on reverse logistics implementation and firm resilience. A proposed model was developed using constructive and reflective constructs with second order analysis. The data was collected from 123 Malaysia automotive industry. The ISO 14001 certified firms have proven moderate the relationship between reverse logistics implementation and firm resilience. The findings contribute to a better understanding in term of critical domains of reverse logistics to safe the manufacturing firms from uncertain business factors and survival. Malaysian automotive industry with the pressure of economic turbulence and quality requirements must be able to manage the sources of raw materials, demand management, production cost and distribution channels to avoid the rising price of automotive products